2012
DOI: 10.1016/j.jchemneu.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Organization and number of orexinergic neurons in the hypothalamus of two species of Cetartiodactyla: A comparison of giraffe (Giraffa camelopardalis) and harbour porpoise (Phocoena phocoena)

Abstract: The present study describes the organization of the orexinergic (hypocretinergic) neurons in the hypothalamus of the giraffe and harbour porpoise – two members of the mammalian Order Cetartiodactyla which is comprised of the even-toed ungulates and the cetaceans as they share a monophyletic ancestry. Diencephalons from two sub-adult male giraffes and two adult male harbour porpoises were coronally sectioned and immunohistochemically stained for orexin-A. The staining revealed that the orexinergic neurons could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 43 publications
12
67
0
Order By: Relevance
“…As this parvocellular orexinergic cluster had not been previously identified in other species, nor had the differences in neuronal numbers and size been reported, Dell et al (2012) concluded that the orexinergic system is potentially more complex in Cetartiodactyla compared to other mammals; however, it is currently unclear whether these novel findings are associated with differences in the terminal networks of the orexinergic system in these species and if differences do occur, whether they have any functional…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…As this parvocellular orexinergic cluster had not been previously identified in other species, nor had the differences in neuronal numbers and size been reported, Dell et al (2012) concluded that the orexinergic system is potentially more complex in Cetartiodactyla compared to other mammals; however, it is currently unclear whether these novel findings are associated with differences in the terminal networks of the orexinergic system in these species and if differences do occur, whether they have any functional…”
Section: Introductionmentioning
confidence: 88%
“…In most mammals the majority of these orexinergic neurons are found within the lateral hypothalamus and perifornical area, but have also been observed in the zona incerta region and the ventrolateral hypothalamus near the optic tract (Peyron et al, 1998;van den Pol, 1999;Wagner et al, 2000;Iqbal et al, 2001;Moore et al, 2001;Yoshida et al, 2006;Nixon and Smale, 2007;Datta and MacLean, 2007;Ettrup et al, 2010;Kruger et al, 2010;Bhagwandin et al, 2011a,b;Gravett et al, 2011;Calvey et al, 2013;Dell et al, 2013;Maseko et al, 2013). A study by Dell et al (2012) comparing the distribution and number of orexinergic neurons in the brain of the giraffe and harbour porpoise showed an additional novel medially located parvocellular cluster of orexinergic neurons in the hypothalamus of these two species, which has since also been reported in the African elephant (Maseko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three exceptions to this organization have been reported in the literature. Both hamsters and microchiropterans appear to lack the optic tract cluster of orexinergic neurons (Mintz et al, 2001;McGranaghan and Piggins, 2001;Korooshi and Klingenspor, 2005;Vidal et al, 2005;Kruger et al, 2010), while the cetartiodactyla, represented by the giraffe and harbour porpoise, are reported to have an additional cluster of parvocellular orexinergic neurons in the medial hypothalamus (Dell et al, 2012). Thus, for the most part, the organization of the orexinergic system is also quite conservative across mammals.…”
Section: The Lack Of Changes In the Serotonergic And Orexinergic Systemsmentioning
confidence: 99%